KARAKTERISTIK SIFAT FUNGSIONAL KACANG HIJAU KUKUS DENGAN VARIASI WAKTU PENGUKUSAN - Trianto, Yoel; Sutedja, Anita Maya; Trisnawati, Chatarina Yayuk (Jurnal Teknologi Pangan dan Gizi, 2013)
Functional properties application of legumes species that including mungbean is basely affected by natural protein and starch complex structure. Steaming become one of several treatments which capable to break complex structure of starch-protein in addition to gelatinize starch and denaturate protein. This become a base of research about the effect of steaming duration on functional properties of mungbean. The factor which will be researched is steaming of mungbean that consists of six levels those are 0 minute, 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes. Applied parameters include protein solubility, water binding capacity, oil binding capacity, foam forming capacity and stability, emulsion forming capacity and stability. The result reported that best treatment in several parameters consist of protein solubility, emulsion capacity and emulsion stability unsteamed mungbean (0 minute of steaming), whereas best treatment for foaming capacity is 1 minute duration of steaming and best treatment for foaming stability is 5 minutes. The best treatment for water binding capacity and oil binding capacity parameters is 3 minutes duration of steaming.